2021
DOI: 10.3390/tomography7040045
|View full text |Cite
|
Sign up to set email alerts
|

Is It Worth Considering Multicentric High-Grade Glioma a Surgical Disease? Analysis of Our Clinical Experience and Literature Review

Abstract: Introduction. The simultaneous presence of multiple foci of high-grade glioma is a rare condition with a poor prognosis. By definition, if an anatomical connection through white matter bundles cannot be hypothesized, multiple lesions are defined as multicentric glioma (MC); on the other hand, when this connection exists, it is better defined as multifocal glioma (MF). Whether surgery can be advantageous for these patients has not been established yet. The aim of our study was to critically review our experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…According to the different types of origin, gliomas can be divided into three types: astrocytoma, oligoastrocytoma and oligodendroglioma ( Davis, 2018 ). Common indicators for prognosis monitoring mainly include 1p/19q codeletion, IDH mutation, G-CIMP phenotype, TP53 mutation, and MGMT methylation ( Baldock et al, 2014 ; Gusyatiner and Hegi, 2018 ; Guerrini et al, 2021 ). IDH mutation is currently recognized as an indicator of better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the different types of origin, gliomas can be divided into three types: astrocytoma, oligoastrocytoma and oligodendroglioma ( Davis, 2018 ). Common indicators for prognosis monitoring mainly include 1p/19q codeletion, IDH mutation, G-CIMP phenotype, TP53 mutation, and MGMT methylation ( Baldock et al, 2014 ; Gusyatiner and Hegi, 2018 ; Guerrini et al, 2021 ). IDH mutation is currently recognized as an indicator of better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that radiotherapy with concurrent TMZ is a potentially feasible treatment option for multifocal GBM. [13] Guerrini et al [6] reported OS of 8.7 months in mGBM (n = 16). Age ≤70 years, a post-operative KPS ≥70, gross or subtotal excision, and adjuvant treatment were shown to be associated with a significantly better prognosis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Age ≤70 years, a post-operative KPS ≥70, gross or subtotal excision, and adjuvant treatment were shown to be associated with a significantly better prognosis. [6] One of the largest studies was reported by Haque et al [14] The authors evaluated demographic and clinical characteristics of solitary and mGBM from National Cancer Database (NCDB) analysis (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). Out of 45,268 total patients, 7785 (17.2%) had multifocal GBM.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations